Maximal power output during incremental cycling test is dependent on the curvature constant of the power-time relationship - Souza, Kristopher Mendes; Lucas, Ricardo Dantas de; Salvador, Paulo Cesar do Nascimento; Guglielmo, Luiz Guilherme Antonacci; Caritá, Renato Aparecido Corrêa [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Canadian Science Publishing, 2015)
The aim of this study was to investigate whether the maximal power output (Pmax) during an incremental test was dependent on the curvature constant (W') of the power-time relationship. Thirty healthy male subjects (maximal oxygen uptake = 3.58 ± 0.40 L·min(-1)) performed a ramp incremental cycling test to determine the maximal oxygen uptake and Pmax, and 4 constant work rate tests to exhaustion to estimate 2 parameters from the modeling of the power-time relationship (i.e., critical power (CP) and W'). Afterwards, the participants were ranked according to their magnitude of W'. The median third was excluded to form a high W' group (HIGH, n = 10), and a low W' group (LOW, n = 10). Maximal oxygen uptake (3.84 ± 0.50 vs. 3.49 ± 0.37 L·min(-1)) and CP (213 ± 22 vs. 200 ± 29 W) were not significantly different between HIGH and LOW, respectively. However, Pmax was significantly greater for the HIGH (337 ± 23 W) than for the LOW (299 ± 40 W). Thus, in physically active individuals with similar aerobic parameters, W' influences the Pmax during incremental testing.
Keywords: Critical power; Cycling; Cyclisme; Endurance; Exercise performance; Fatigue; Performance physique; Puissance critique; Ramp incremental test; Test d’effort progressif